2013
DOI: 10.1007/978-3-642-39179-8_19
|View full text |Cite
|
Sign up to set email alerts
|

Agile Maturity Model: A Synopsis as a First Step to Synthesis

Abstract: The paper describes the current status of agile maturity models. It shows where such models can be found and it contains a structured top level compilation of the currently available agile maturity models. In the second section, the paper describes an approach to analyse these agile maturity models, extracts their content, maps it to a reference model and then synthesizes the real agile maturity issues. The paper also describes the needs for scientific research in this topic. The paper will not present its own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In a systematic review of literature, Schweigert et al identifies around 40 maturity models for agile development. The analysis concluded that, despite an urgent need for agile maturity models, currently none of the models proposed in the literature is widely referred in practice and academia.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In a systematic review of literature, Schweigert et al identifies around 40 maturity models for agile development. The analysis concluded that, despite an urgent need for agile maturity models, currently none of the models proposed in the literature is widely referred in practice and academia.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Besides, as stated before, during our review process we have not been able to gather any work analyzing the relation among Agile, Web Engineering and CMMI on its continuous representation. Lastly, despite we were able to identify papers studying Agile Maturity Models like [48] and [49], none of them are providing the Web dimension. As a conclusion, these three aspects (the relation among Agile, Web Engineering and ISO/IEC process standards, CMMI continuous representation and Agile Maturity Models) remain as three open research areas to further development.…”
Section: Discussionmentioning
confidence: 93%
“…They found almost all of the inspected models being independently defined from any agile method, yet all inspected models show deficiencies, notably regarding completeness of the models, correctness and consistency, and the definition of agility levels. Similarly, Schweigert et al analyzed the state of the art concerning agile maturity models. The authors analyzed a subset of approximately 40 agile maturity models and concluded that there is no consensus about a model for agile maturity.…”
Section: Background and Related Workmentioning
confidence: 99%